2022
DOI: 10.1038/s41467-022-29315-3
|View full text |Cite
|
Sign up to set email alerts
|

The phytochrome interacting proteins ERF55 and ERF58 repress light-induced seed germination in Arabidopsis thaliana

Abstract: Seed germination is a critical step in the life cycle of plants controlled by the phytohormones abscisic acid (ABA) and gibberellin (GA), and by phytochromes, an important class of photoreceptors in plants. Here we show that light-dependent germination is enhanced in mutants deficient in the AP2/ERF transcription factors ERF55 and ERF58. Light-activated phytochromes repress ERF55/ERF58 expression and directly bind ERF55/ERF58 to displace them from the promoter of PIF1 and SOM, genes encoding transcriptional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…The TFs are considered as ideal candidates for crop improvement because their overexpression enhances tolerances to multiple abiotic and biotic stresses in transgenic plants [ 25 ]. Extensive studies have demonstrated that AP2/ERF TFs are crosstalk factors in stress signal pathways involved in salicylic acid, jasmonic acid, ethylene, and abscisic acid signal transduction pathways [ 26 ], and hence play vital roles in regulating plant growth and development as well as in response to diverse stresses [ 27 , 28 ]. Although AP2/ERF TFs have been thoroughly identified and characterized in many plant species, very little is known about the AP2/ERF gene family in ramie.…”
Section: Discussionmentioning
confidence: 99%
“…The TFs are considered as ideal candidates for crop improvement because their overexpression enhances tolerances to multiple abiotic and biotic stresses in transgenic plants [ 25 ]. Extensive studies have demonstrated that AP2/ERF TFs are crosstalk factors in stress signal pathways involved in salicylic acid, jasmonic acid, ethylene, and abscisic acid signal transduction pathways [ 26 ], and hence play vital roles in regulating plant growth and development as well as in response to diverse stresses [ 27 , 28 ]. Although AP2/ERF TFs have been thoroughly identified and characterized in many plant species, very little is known about the AP2/ERF gene family in ramie.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ERF-type transcription factors ERF55/ERF58 play a negative role in light-regulated seed germination. Light-activated PHYA and PHYB repress the expression of ERF55/ERF58 ; furthermore, PHYA and PHYB interact with ERF55/ERF58 and inhibit their binding activity upon the downstream targets, leading to promoted seed germination [ 35 ]. These findings suggest that PHYB promotes seed germination through regulating multiple downstream light-responsive factors.…”
Section: Discussionmentioning
confidence: 99%
“…The combined supernatant fractions were directly measured using targeted LC–MS. The LC–MS analysis was performed as described previously 55 except for using a Luna Omega Polar C18 column (3 μm; 100 Å; 150 × 0.5 mm; Phenomenex), a Luna C18(2) trap column (5 μm; 100 Å; 20 × 0.5 mm; Phenomenex) with an increased column temperature of 55 °C and a flow rate of 28 µl min −1 for the main column. The ABA content in a sample was normalized against the D6-ABA values.…”
Section: Methodsmentioning
confidence: 99%